How To (Un)Globe the Earth in Four Easy Lessons. - Miller, J. Hillis (Substance: A Review of Theory & Literary Criticism, 2012)
The article explores the various definitions and connotations of Earth-related words. The author explains the phrase, globing the earth, a combination of two common words in English used to name the whole planet. He explains why French philosopher Jacques Derrida prefers the French neologism "modialisation" to the English word, globalization. He ponders the religious connotation of the word, globe and concludes that climate change should be understood as a mechanical process.